Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1136/hrt.59.6.685
|View full text |Cite
|
Sign up to set email alerts
|

Importance of ancillary properties of beta blockers in angina: a study of celiprolol and atenolol.

Abstract: SUMMARY Celiprolol (400 mg) and atenolol (100 mg) were given once a day to 16 patients with stable angina pectoris in a double blind placebo controlled crossover study. Celiprolol produced less suppression of heart rate both at rest and during exercise than atenolol. Both drugs were equally effective in reducing the frequency of angina and in delaying the onset of ischaemia during exercise. Radionuclide ventriculography showed that atenolol but not celiprolol lowered cardiac output at rest and during exercise.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…duction Impaired baroreceptor and cardiopulmonary reflexes; syncope of unknown cause Decreased liver blood flow May need decreased dose of beta blockers, especially in smokers, not relevant to beta blockers primarily excreted by kidneys (applies to propranolol and metoprolol, not to atenolol, nadolol, and celiprolol). When glomerular filtration rate falls substantially (e.g., [25][26][27][28][29][30][31][32][33][34][35] ml/min), dose of water-soluble beta-blocker needs reduction (atenolol, nadolol, and celiprolol). Regarded by some as rationale for nombeta-blocker therapy in the elderly.…”
Section: Change Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…duction Impaired baroreceptor and cardiopulmonary reflexes; syncope of unknown cause Decreased liver blood flow May need decreased dose of beta blockers, especially in smokers, not relevant to beta blockers primarily excreted by kidneys (applies to propranolol and metoprolol, not to atenolol, nadolol, and celiprolol). When glomerular filtration rate falls substantially (e.g., [25][26][27][28][29][30][31][32][33][34][35] ml/min), dose of water-soluble beta-blocker needs reduction (atenolol, nadolol, and celiprolol). Regarded by some as rationale for nombeta-blocker therapy in the elderly.…”
Section: Change Commentmentioning
confidence: 99%
“…These data suggest that celiprolol increases cardiac function with little or no change in heart rate and that it has an indirect positive inotropic effect. In patients with stable angina pectoris [31], celiprolol had an equal antianginal effect, as did atenolol (as judged by exercise stress testing), yet heart rate and cardiac output were higher.…”
Section: Hemodgnamic Changes With Agementioning
confidence: 99%
“…Fig. This was possibly related to ~2agonism and/or direct vasodilator activity [62]. Effect of celiprolol on myocardial oxygen demand and heart rate in patients with stable angina pectoris.…”
mentioning
confidence: 95%
“…This suggests an adverse effect on myocardial oxygen consumption for cardiac work at a given pressure [62]. 2.…”
mentioning
confidence: 99%
“…In both in-vitro and in-vivo studies, celiprolol was shown to possess partial agonist activity (PAA), a property that attenuates the depression of myocardial chronotropy and inotropy associated with beta blockers that lack this property [14][15][16]. Thus, compared with beta blockers that do not possess PAA, celiprolol is less likely to produce sinus bradycardia or myocardial depression.…”
mentioning
confidence: 99%